Rapid sequence intubation in Scottish urban emergency departments. Issue 1 (1st January 2003) - Graham, C A; Beard, D; Oglesby, A J; Thakore, S B; Beale, J P; Brittliff, J; Johnston, M A; McKeown, D W; Parke, T R J
Abstract : Objective: Airway care is the cornerstone of resuscitation. In UK emergency department practice, this care is provided by anaesthetists and emergency physicians. The aim of this study was to determine current practice for rapid sequence intubation (RSI) in a sample of emergency departments in Scotland. Methods: Two year, multicentre, prospective observational study of endotracheal intubation in the emergency departments of seven Scottish urban teaching hospitals. Results: 1631 patients underwent an intubation attempt in the emergency department and 735 patients satisfied the criteria for RSI. Emergency physicians intubated 377 patients and anaesthetists intubated 355 patients. There was no difference in median age between the groups but there was a significantly greater proportion of men (73.2% versus 65.3%, p=0.024) and trauma patients (48.5% versus 37.4%, p=0.003) in the anaesthetic group. Anaesthetists had a higher initial success rate (91.8% versus 83.8%, p=0.001) and achieved more good (Cormack-Lehane Grade I and II) views at laryngoscopy (94.0% versus 89.3%, p=0.039). There was a non-significant trend to more complications in the group of patients intubated by emergency physicians (8.7% versus 12.7%, p=0.104). Emergency physicians intubated a higher proportion of patients with physiological compromise (91.8% versus 86.1%, p=0.027) and a higher proportion of patients within 15 minutes of arrival (32.6% versus 11.3%, p<0.0001). Conclusion: Anaesthetists achieve more good views at laryngoscopy with higher initial success rates during RSI. Emergency physicians perform RSI on a higher proportion of critically ill patients and a higher proportion of patients within 15 minutes of arrival. Complications may be fewer in the anaesthetists' group, but this could be related to differences in patient populations. Training issues for RSI and emergency airway care are discussed. Complication rates for both groups are in keeping with previous studies.